Strategi Manajemen Guru Dalam Meningkatkan Minat dan Bakat Siswa - Octaviani, Octaviani; Sadad, Roihan; Fadhilah, Daniatun Nur; Tamara, Tamara (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
This research aims to determine the concepts of teacher management strategies and efforts to increase student interest and talent. The research method uses qualitative research methods with a library research approach. Researchers conduct studies using library literature in the form of books, encyclopedias, dictionaries, journals, documents, magazines, and so on. The results are: The concept of teacher management strategy is a teacher's ability to plan, organize, implement, supervise, evaluate, and control a plan or effort towards long-term goals so that these goals can be achieved in accordance with what has been set. Efforts to increase students' interests and talents are realized through stimulation or stimuli provided by both parents and teachers, which can generate interest and talents in students so that they become meaningful contributions as motivation for them. If the stimulation they receive is in accordance with their interests and talents, they can grow and develop optimally without coercion, so the stimulation process will be easier to carry out.